Institutional Innovations in Public Agricultural Research in Five Developed Countries - Janssen, Willem G. (International Service for National Agricultural Research, 2002)
All over the world, agricultural research systems are undergoing significant changes. Using an analytical framework, this Briefing Paper describes how research systems adapt to the changes in the context of agricultural research and also, how such adjustments have affected the effectiveness of the research systems in the following five developed countries: the USA, Australia, Switzerland, the Netherlands, and the UK. The conclusion is that the traditional ""technology factories"" are changing into flexible and versatile ""sources of knowledge."" The transformations have not come about easily, but they have helped minimize budget cuts. The new research systems are a reflection of the new conditions that society imposes on agriculture, science, and the management of the public sector.